Granitic series and their economic geology - Kerber, Paulo Augusto (Rhodes University, Faculty of Science, Department of Geology, 1993)
The granitic rocks are subdivided into four series: tholeiitic, alkaline, calc-alkaline and mobilizates. These series can be formed from melting of mantle material (M-type granites) or from crustal rocks. There are granitic rocks formed from the mixing of these two magmas types. The rocks formed from crustal anatexis are subdivided into those formed from igneous rocks (I-type granites) and those formed from meta-sedimentary rocks (S-type granites). The former has similar characteristics to the mantle-derived granitoids. The mineral deposits related to igneous or mantle derived magma usually are Cu-Au, CUI Cu-Mo, Mo porphyries and have high oxygen fugacity and magnetic susceptibility (magnetite series). The Sn-W deposits usually are related to magma derived from meta-sedimentary or igneous rocks derived magma with low oxygen fugacity and magnetic susceptibility (ilmenite series). According to the tectonic setting, the granitoids rocks are classified as: Andino type, West Pacific type, Hercyno type, Caledonian type and Anorogenic (A-type granites).
Keywords: Granite; Geology, Economic